2006
DOI: 10.1111/j.1572-0241.2006.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Encapsulated Probiotic Bifidobacterium infantis 35624 in Women with Irritable Bowel Syndrome

Abstract: B. infantis 35624 is a probiotic that specifically relieves many of the symptoms of IBS. At a dosage level of 1 x 10(8) cfu, it can be delivered by a capsule making it stable, convenient to administer, and amenable to widespread use. The lack of benefits observed with the other dosage levels of the probiotic highlight the need for clinical data in the final dosage form and dose of probiotic before these products should be used in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
561
1
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(622 citation statements)
references
References 38 publications
20
561
1
23
Order By: Relevance
“…Moreover, it has been seen that, in vitro human dendritic cells stimulated with B. infantis selectively promoted the upregulation of FoxP3 expression in naïve lymphocytes [89]. Furthermore, B. infantis has been demonstrated to reduce symptom severity in patients with inflammatory bowel syndrome in two placebo-controlled human clinical studies [91,92].…”
Section: Use Of Probiotics For the Induction Of Regulatory T Cellsmentioning
confidence: 99%
“…Moreover, it has been seen that, in vitro human dendritic cells stimulated with B. infantis selectively promoted the upregulation of FoxP3 expression in naïve lymphocytes [89]. Furthermore, B. infantis has been demonstrated to reduce symptom severity in patients with inflammatory bowel syndrome in two placebo-controlled human clinical studies [91,92].…”
Section: Use Of Probiotics For the Induction Of Regulatory T Cellsmentioning
confidence: 99%
“…Several trials have been excluded from this list because of failure to compare with placebo (49) , re-analysis of old data (50) , unclear end points (51) or the use of multiple interventions (52) . Many early studies were small singlecentre trials (53)(54)(55)(56)(57) , although more recently a number of much larger multi-centre trials have been undertaken, reflecting the growing interest in the area (58)(59)(60)(61) .…”
Section: Probiotics In Irritable Bowel Syndrome: Clinical Trialsmentioning
confidence: 99%
“…Results from three randomized, controlled studies of B infantis 35624 indicated that some baseline symptoms of IBS improved after a 4-or 8-week course of daily B infantis 35624 therapy [75][76][77]. In a double-blind, placebo-controlled study, patients with IBS who were randomly assigned to receive B infantis 35624 capsules daily did not experience significant improvements in individual symptoms of IBS (i.e.…”
Section: Bifidobacterium Infantis 35624mentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled, doseranging study of B infantis 35624 capsule administered once daily (range, 1 × 10 6 to 1 × 10 10 cells/dose) for 4 weeks, females with IBS (n = 362) who received B infantis 1 × 10 8 cells/dose (n = 90) experienced significant improvement from baseline in abdominal pain/discomfort after 4 weeks of treatment (P = 0.02) [76]. Further, patients who received B infantis 1 × 10 8 cells/dose experienced significant improvement from baseline in bloating/distension, sense of incomplete evacuation, flatulence, straining, and satisfaction with bowel habit compared with placebo [76].…”
Section: Bifidobacterium Infantis 35624mentioning
confidence: 99%